Identification of MspI Polymorphism in the Forth Intron of Chicken Growth Hormone Gene and Their Associations with Growth Traits in Indonesia Native Chickens - Mu’in, MA; Lumatauw, S (ANIMAL PRODUCTION, 2013)
Abstract. The objective of this research was to identify MspI polymorphism in the forth intron of chicken growth hormone (cGH) gene and their associations with growth traits in native Indonesian chickens. A total of 72 Indonesia native chickens were genotyped for a locus in the forth intron of cGH gene (cGH-I4/MspI locus) by PCR-RFLP with MspI restriction enzyme. The result showed two genotypes in this locus: AA and BB, with the frequency of 90.28% and 9.72%, respectively. Based on body weight average, B allele had a beneficial effect in increasing the live body weight. The result of General Linier Models analysis indicated that the polymorphism of this locus had significant association (P<0.05) with body weight at 4 months of age and so did the daily gain between 2 to 4 months of age. Therefore, these results suggest that there is a possibility of cGH-I4/MspI locus acting as a genetic marker for growth traits of native Indonesian chickens, especially for body weight at 4 months and daily gain between 2 to 4 months of age.Â Keywords: polymorphism, cGH gene, growth traits, Indonesia native chickens.Â Abstrak.Â  Tujuan dari penelitian ini adalah untuk mengidentifikasi polimorfisme MspI intron ke-4 pada gen hormon pertumbuhan ayam (cGH) dan hubungannya dengan sifat pertumbuhan pada ayam asli Indonesia. Sebanyak 72 ekor ayam asli Indonesia diidentifikasi gentotipenya untuk lokus pada intron ke-4 dari gen cGH (cGH-I4/MspI lokus) dengan PCR-RFLP mengguakan enzim restriksi MspI. Hasil penelitian menunjukkan adanya dua genotipe pada lokus ini: AA dan BB , dengan frekuensi masing-masing 90.28 % dan 9,72 %. Berdasarkan rata-rata bobot badan, alel B memiliki pengaruh yang menguntungkan dalam meningkatkan bobot badan hidup. Hasil analisis General Linier Model menunjukkan bahwa polimorfisme lokus ini memiliki hubungan yang nyata (P<0,05 ) dengan bobot badan pada umur 4 bulan dan begitu pula dengan pertambahan bobot badan harian antara umur 2 sampai 4 bulan. Oleh karena itu, hasil ini menunjukkan bahwa ada kemungkinan cGH-I4/MspI lokus bertindak sebagai penanda genetik untuk sifat pertumbuhan ayam asli Indonesia, terutama untuk bobot badan pada umur 4 bulan dan pertambahan bobot badan harian ayam antara umur 2 sampai 4 bulan.Â Kata kunci: polimorfisme , gen cGH , sifat pertumbuhan , ayam asli Indonesia.MA Muâin and S Lumatauw/Animal Production 15(1):1-7, January 2013